Decline In Character Of Generation Z: The Mediation Effect Of Smartphone Use, Parental Attention, and Peer Environment - Muh. Nur Rochim Maksum; Triono Ali Mustofa; Dartim; Surya Jatmika; Viky Nur Vambudi; Muhammad Zidan Nur Ihsan; Sofiy Zaini Al Irfani (Edudeena : Journal of Islamic Religious Education, 2026)
The development of digital technology has changed the social interaction patterns of Generation Z adolescents, especially due to the intensive use of smartphones, which has resulted in concerns of character degradation. This study aims to analyze the mediating role of smartphone use in the relationship between parental attention and peer environment towards character degradation of adolescents aged 14-19 years in Surakarta. The approach used in this study is a quantitative approach with explanatory design through Structural Equation Modeling (SEM) and a bias-corrected (BCa)-based bootstrap mediation test to identify direct and indirect influences between constructions. The results of the analysis showed that parental attention had a significant negative effect on character degradation (β = -0.321, p < 0.001) and smartphone use (β = -0.412, p < 0.001), which indicates the protective role of the family. In contrast, peer environment had significant positive effects on smartphone use (β = 0.486, p < 0.001) and character degradation (β = 0.571, p < 0.001). The indirect effect of parental attention to character degradation through smartphone use was also significant (β = -0.159, p = 0.032; 95% BCa CI [-0.720, -0.010]), suggesting partial mediation, whereas smartphone use fully mediated the relationship between peer environment and character degradation (β = 0.278, p = 0.041). These findings confirm that smartphone use serves as a central mechanism that connects family and social contexts with adolescent character degradation, so these findings can enrich the study of digital behavior, especially in understanding the dynamics of Generation Z character formation.